ICOH Statement on Protecting the Occupational Safety and Health of Migrant Workers (Elsevier, 2022)
Globally, it is estimated that the number of people living outside of their country of origin reached 281 million in 2020. The primary drive of those migrants when migrating voluntarily is work to increase their income and provide for their families left behind in their home countries. Those who migrate immediately seek means of income to sustain themselves through a perilous process as currently evidenced in the war in Ukraine and not too long ago in Syria and Venezuela. Unfortunately, migrant workers are globally known to predominantly be working in "4-D jobs"- dirty, dangerous, and difficult and discriminatory; the fourth D was recently added to acknowledge the discriminatory aspect and other social determinants of health migrant workers face in their host country while exposed to precarious work. Consequently, migrant workers are at considerable risk of work-related illnesses and injury but their health needs are critically overlooked in research and policy. Recognizing the UN Universal Declaration of Human Rights "Everyone has the right to work, to free choice of employment, to just and favourable conditions of work and to protection against unemployment", we cannot consider any human life - thus, the life of migrant workers - as dispensable through a structural discriminatory process that undervalues their occupational safety and health, livelihood and the contribution these workers bring to their host countries. This was seen during the preparation for the upcoming world cup in Qatar where migrant workers were exposed to a multiplicity of serious hazards including deadly heat hazards.